Professional commitment as moderating the influence of idealism and experience on ethical decision making of tax consultants at IKPI Malang Branch - Dewi Ernawati; Dwi Orbaningsih; Oyong Lisa (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
This study aims to examine and analyze: 1) the influence of idealism on ethical decisions, 2) the influence of experience on ethical decisions, 3) professional commitment moderates the relationship of idealism to ethical decisions, 4) professional commitment moderates the influence of experience on ethical decisions. This research was conducted at the Malang Branch of the Indonesian Tax Consultant covering 13 regencies/cities in March – July 2022. The population is 110 employees at the Consultant. The sample was determined by convenience sampling, obtained a sample of 91 respondents. Primary data is obtained by sending questionnaires to respondents through goole form. Once the data is collected, it is analyzed by moderation double linear regression. Before analysis, a classical assumption test is carried out. To test the hypothesis used t-test. The results proved that: 1) idealism affects ethical decisions, 2) experience influences ethical decisions, 3) the interaction of professional commitment with idealism is unable to moderate its influence on ethical decisions , 4) the interaction of professional commitment with experience is able to moderate (weaken) its influence on ethical decisions.